2017
DOI: 10.1016/j.radonc.2017.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Dose-volume correlates of mandibular osteoradionecrosis in Oropharynx cancer patients receiving intensity-modulated radiotherapy: Results from a case-matched comparison

Abstract: Purpose To determine dosimetric parameters associated with Osteoradionecrosis (ORN) in oropharyngeal cancer (OPC) patients in the IMRT era. Material and Methods Subsequent to institutional review board approval, we identified ORN in OPC patients treated with IMRT from 2002–2013. 1:2 case-control matching was implemented. Mandibular dose-volume histograms (DVH) were extracted. Dosimetric parameters were compared using non-parametric stats. Recursive partitioning analysis (RPA) was done to identify DVH correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 32 publications
4
56
1
Order By: Relevance
“…Consequently, it remains unclear which dosimetric parameters should be considered to minimize the ORN risk [24] . A recent case-matched comparison of only IMRT treated patients, showed that all doses in the intermediate and high range were more likely to be elevated in the ORN patients compared to asymptomatic controls [25] . These findings suggested that, to reduce ORN incidence, in IMRT treatment planning, whenever feasible, several volumetric constraints should be utilized, rather than a single point-dose maximum as in the pre-IMRT era.…”
Section: Controversies – Radiation Therapy and Toxicitymentioning
confidence: 99%
“…Consequently, it remains unclear which dosimetric parameters should be considered to minimize the ORN risk [24] . A recent case-matched comparison of only IMRT treated patients, showed that all doses in the intermediate and high range were more likely to be elevated in the ORN patients compared to asymptomatic controls [25] . These findings suggested that, to reduce ORN incidence, in IMRT treatment planning, whenever feasible, several volumetric constraints should be utilized, rather than a single point-dose maximum as in the pre-IMRT era.…”
Section: Controversies – Radiation Therapy and Toxicitymentioning
confidence: 99%
“…Peterson et al reported the prevalence of established ORN as 7% with conventional radiotherapy and 5% with IMRT. A recent case‐matched comparison study of only IMRT treated oropharyngeal cancer patients showed that individuals in the ORN group had received higher doses of radiotherapy compared to asymptomatic controls . In our study, although all recruited patients were treated with IMRT, five (17%) and two (7%) patients had an established and new ORN, respectively.…”
Section: Discussionmentioning
confidence: 43%
“…A recent case-matched comparison study of only IMRT treated oropharyngeal cancer patients showed that individuals in the ORN group had received higher doses of radiotherapy compared to asymptomatic controls. 26 In our study, although all recruited patients were treated with IMRT, five (17%) and two (7%) patients had an established and new ORN, respectively. All seven participants with the ORN had cancer localized to the oral cavity where the mandible would have been included and would have received the maximum dose.…”
Section: Patients' Oral Health Statusmentioning
confidence: 59%
“…With regard to photon RT, high-dose irradiation to the mandible has been reported previously as a risk factor for ORN. 11 , 12 The MD Anderson Head and Neck Cancer Symptom Working Group 12 reported the dosimetric parameters associated with ORN in 199 patients with oropharyngeal cancer treated with photon RT. In the study, the mandibular mean dose was significantly higher in the ORN cohort compared with the non-ORN cohort (48.1 vs 43.6 Gy; P < .0001).…”
Section: Discussionmentioning
confidence: 99%